Intensifying agriculture in Southern Bangladesh: unlocking mungbean productivity through innovative management practices - Hossain, Md. Khaled; Atikuzzamman, Md.; Anisur Rahaman; Laing, Alison M.; Krupnik, Timothy J. (AMD, 2024)
The study demonstrates that adopting BARC-recommended fertilizer rates, combined with rhizobium seed inoculation, significantly increases mungbean yields and profitability compared to current farmer practices. Treatments T3 (BARC-recommended fertilizer) and T4 (BARC-recommended fertilizer with rhizobium inoculation) produced the highest yields and gross margins, with T4 showing a synergistic effect between fertilizer and rhizobium inoculation. While rhizobium inoculation was effective in enhancing productivity, variability in its performance among farmers suggests the need for consistent application methods and training. Despite the profitability of these practices, broader adoption is limited by factors such as resource availability, and farmers’ limited knowledge about the benefits and application of these improved practices.